What can seismic in hard rocks do for you? - Urosevic, Milovan (CSIRO, 2013)
As the search for mineral deposits moves to greater depths, seismic methods, with its penetration ability and unmatched resolution power, are becoming more important tool for exploration of mineral resources underneath the deep cover. However the performance of seismic appears to be still inconsistent which prevents it from becoming the primary exploration method in the mineral sector, similar to its role in oil exploration. The performance of seismic methods is affected by complex geology, excessive ambient noise, access restriction, weak reflectivity and/or low signal to noise ratio, limited acquisition program due to cost restriction, etc. Two other factors are emerging recently as important: a) lack of correlation of seismic images and b) miss-match between survey design and target characteristics. The first one is the greatest threat to the affirmation of seismic in the mineral sector as it prevents seismic images to be utilised in any constructive way. The second one translates to the use of simplified 2D geometries to delineate complex 3D structures which may cause seismic to underperform. On the positive side there are clearly favourable cases for the application of reflection seismic. Those can be primarily related to the massive, concentrated mineralisation such are massive sulphides. The less favourable geological settings require much more elaborate analysis to allow seismic method to perform. It appears that the lack of understanding of the complexity and the variability of seismic responses in different geological settings is what still prevents the widespread use of this method for mineral exploration. In general seismic could be useful in different ways, from regional to deposit scale and from exploration to production stage.